Optimization of Building Exit Layout: Combining Exit Decisions of Evacuees - Guofeng Ma; Yuqi Wang; Shan Jiang (Advances in Civil Engineering)
Exits are essential to the efficiency of building evacuation due to its irreplaceable function, and the layout of multiple exits has always been the key concern for architectural design. To accurately evaluate the evacuation efficiency of different multiexit layouts and optimize the design rules, a dynamic exit decision model integrating an exit selection strategy and the social force model is developed to simulate the practical evacuation. And our proposed model outperforms the original social force model in terms of evacuation efficiency. Accordingly, different layouts are analyzed for evacuation in a single room with two exits. The analysis results reveal that evacuation time will be improved with the changes of exit locations and two parallel exits are validated as the most efficient layout among the three common categories. Affected by walking time and queuing time of evacuees, it is not conducive to evacuation whether the separation of two exits is too large or too small. Furthermore, an even symmetry is found more efficient than an asymmetric distribution of exits under some conditions. This work provides a basis for architectural designs of multiple exits and a foundation for further study of evacuation simulation.